Remote-Microphone Benefit in Noise and Reverberation for Children Who are Hard of Hearing - Lewis, Dawna; Spratford, Meredith; Stecker, G. Christopher; McCreery, Ryan W. (Journal of the American Academy of Audiology, 2022)
Background Remote-microphone (RM) systems are designed to reduce the impact of poor acoustics on speech understanding. However, there is limited research examining the effects of adding reverberation to noise on speech understanding when using hearing aids (HAs) and RM systems. Given the significant challenges posed by environments with poor acoustics for children who are hard of hearing, we evaluated the ability of a novel RM system to address the effects of noise and reverberation.Purpose We assessed the effect of a recently developed RM system on aided speech perception of children who were hard of hearing in noise and reverberation and how their performance compared to peers who are not hard of hearing (i.e., who have hearing thresholds no greater than 15 dB HL). The effect of aided speech audibility on sentence recognition when using an RM system also was assessed.Study Sample Twenty-two children with mild to severe hearing loss and 17 children who were not hard of hearing (i.e., with hearing thresholds no greater than 15 dB HL) (7–18 years) participated.Data Collection and Analysis An adaptive procedure was used to determine the signal-to-noise ratio for 50 and 95% correct sentence recognition in noise and noise plus reverberation (RT 300 ms). Linear mixed models were used to examine the effect of listening conditions on speech recognition with RMs for both groups of children and the effects of aided audibility on performance across all listening conditions for children who were hard of hearing.Results Children who were hard of hearing had poorer speech recognition for HAs alone than for HAs plus RM. Regardless of hearing status, children had poorer speech recognition in noise plus reverberation than in noise alone. Children who were hard of hearing had poorer speech recognition than peers with thresholds no greater than 15 dB HL when using HAs alone but comparable or better speech recognition with HAs plus RM. Children with better-aided audibility with the HAs showed better speech recognition with the HAs alone and with HAs plus RM.Conclusion Providing HAs that maximize speech audibility and coupling them with RM systems has the potential to improve communication access and outcomes for children who are hard of hearing in environments with noise and reverberation.
Keywords: children; hearing aids and amplification devices; hearing loss; speech perception; room acoustics